Cryptosporidium in human-animal-environment interphase at Adama and Asella areas of Oromia regional state, Ethiopia - Kassahun Berhanu; Dinka Ayana; Bekele Megersa; Hagos Ashenafi; Hika Waktole (BMC Veterinary Research, 2022)
Abstract Background In Ethiopia, several studies have reported the occurrence of Cryptosporidium infection in young calves, lambs, and HIV positive patients. However, research on cattle and sheep of all ages, as well as humans, has been limited. Methods A cross-sectional study was conducted to investigate the occurrence of Cryptosporidium in dairy cattle, sheep, humans, and manure samples. Dairy cattle and sheep were stratified according to their age groups and randomly sampled. Stool samples from volunteered dairy farm workers and rural household members were collected purposefully. A semi-structured questionnaire was also used to collect information about manure handling practices and socio-demographic variables. All collected samples were processed with the sugar floatation technique and the modified Ziehl–Neelsen staining method. Logistic regression was used to analyze the association of risk factors with the occurrence of Cryptosporidium in study subjects (p < 0.05). Results The overall prevalence of Cryptosporidium in dairy cattle, sheep, humans, and manure samples was 20.5%, 14%, 16%, and 13.20%, respectively. Cryptosporidium infection was significantly higher in dairy cattle aged 1–12 months and 13–36 months with odds of 3.48 and 3.07 times higher, respectively, compared to others. Similarly, its occurrence was 2.69 times higher in sheep aged 1–6 months than those above 6 months. And also, a higher average oocyst count (above 10 oocysts) per-field was observed in cattle aged 1–12 months, followed by sheep aged 1–6 months. Furthermore, the likelihood of infection was 13 times greater in farm workers compared to household members of smallholder farmers. In addition, the occurrence of oocysts was 22.8 times higher in manures from dairy cattle than that of sheep. About 16.8% of the study respondents had manure disposal pit, 98.1% of them used manure as fertilizer for crop and vegetable production without any treatment. Conclusions The study revealed the occurrence of Cryptosporidium infection in all age groups of dairy cattle and sheep, humans engaged in animal production. Occurrence of Cryptosporidium in manure suggests it potential contamination of environment and water sources.